2022
DOI: 10.1073/pnas.2113936119
|View full text |Cite
|
Sign up to set email alerts
|

Population interconnectivity over the past 120,000 years explains distribution and diversity of Central African hunter-gatherers

Abstract: Significance We combined ethnographic, archaeological, genetic, and paleoclimatic data to model the dynamics of Central African hunter-gatherer populations over the past 120,000 years. We show, against common assumptions, that their distribution and density are explained by changing environments rather than by a displacement following recent farming expansions, and that they have maintained large population sizes and genetic diversity, despite fluctuations in niche availability. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 73 publications
1
34
0
Order By: Relevance
“…Recent ecological, genetic and archaeological analyses have cast doubt on this interpretation, revealing various signs of long-term adaptation of CAHGs to current environments and independence from Bantu demographic history. For example, Padilla-Iglesias et al 19 have shown that ecological and climatic features of the Congo Basin can successfully predict 120,000 years of hunter-gatherer between-group interconnectivity and continuous forest occupation, in agreement both with archaeological evidence 20 and the deep genetic coalescence of CAHGs with other human lineages 21,3 .…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Recent ecological, genetic and archaeological analyses have cast doubt on this interpretation, revealing various signs of long-term adaptation of CAHGs to current environments and independence from Bantu demographic history. For example, Padilla-Iglesias et al 19 have shown that ecological and climatic features of the Congo Basin can successfully predict 120,000 years of hunter-gatherer between-group interconnectivity and continuous forest occupation, in agreement both with archaeological evidence 20 and the deep genetic coalescence of CAHGs with other human lineages 21,3 .…”
Section: Introductionmentioning
confidence: 81%
“…The significant correlation between the distribution of subsistence tools and local ecological conditions provides strong evidence for long-term adaptation of CAHG groups to forest environments in the Congo basin. The deep adaptive history of foraging tools may explain why ecological variables can successfully predict the distribution of both current and past hunter-gatherers in Central Africa 19 .…”
Section: Discussionmentioning
confidence: 99%
“…1 to 4) are obtained for the conservative dataset, and sensitivity experiments with the other data are shown in the supplementary materials. By comparing the corresponding species distribution predictions generated with the three datasets, we gain very similar insights while addressing in part the effect of potential preservation biases ( 19 , 20 ), which are presumably very pronounced in the Asian monsoon region.…”
Section: Neanderthal and Denisovan Habitatsmentioning
confidence: 86%
“…S2). The warm and humid conditions of the Southeast Asia monsoon region may have further limited the preservation potential ( 19 , 20 ), which led to the current paucity of fossil remains there. Unfortunately, this scarcity of fossil remains has made it difficult to draw further conclusions regarding their spatiotemporal distribution and possible encounters with other archaic hominins.…”
mentioning
confidence: 99%
“…The availability of such data paved the way for a large number of research questions among many disciplines, i.e. ecology (Miller et al 2021b, VanBuren and Jarzyna 2022), paleoecology (Leonardi et al 2018, 2022, Somveille et al 2020, Chen et al 2021, Schap et al 2021, Thorup et al 2021, Medina‐Castañeda et al 2022, Reade et al 2022), conservation (Beyer and Manica 2021), population genetics (Maisano Delser et al 2021, Miller et al 2021a, Warmuth et al 2021), archaeology (Betti et al 2020, Racimo et al 2020, Beyer et al 2021, Krzyzanska et al 2021, Bradshaw et al 2022, Cerasoni et al 2022, Park and Marwick 2022, Timbrell et al 2022), macroevolution of different taxa, including the genus Homo (Saupe et al 2014, Will et al 2021, Fordham et al 2022, Timmermann et al 2022, Troyer et al 2022), anthropology (Leonardi et al 2017, Padilla‐Iglesias et al 2022) and linguistics (Beyer et al 2019).…”
Section: Introductionmentioning
confidence: 99%